Online loan phenomenon among students: micro and macro psychological analysis: Fenomena pinjaman online di kalangan mahasiswa: analisis psikologi mikro dan makro - Islakhul Muttaqin; Lusi Nuryanti (Talenta Publisher, 2023)
This study specifically examines the impact of online loans and analyzes both micro and macro psychological aspects. The quantitative respondents consist of 124 participants, while the qualitative research involves two informants for observation and interviews. The findings of this study indicate that the emergence of online loans is attributed to the ease of regulations, leading many students to fall into the trap of online borrowing. Peer influence and lifestyle are the main factors that lead students to utilize online lending services. Being the closest social environment, Peers influence lifestyle changes, and online loans become a means to meet those lifestyle needs. On the other hand, from the macro psychological perspective, regulations, and social media play a significant role in influencing students to opt for online loans.